The First Extracellular Linker Is Important for Several Aspects of the Gating Mechanism of Human TRPA1 Channel - Marsakova, Lenka; Barvik, Ivan; Zima, Vlastimil; Zimova, Lucie; Vlachova, Viktorie (Frontiers in molecular neuroscience, 2017)
Transient receptor potential ankyrin 1 (TRPA1) is an excitatory ion channel involved in pain, inflammation and itching. This channel gates in response to many irritant and proalgesic agents, and can be modulated by calcium and depolarizing voltage. While the closed-state structure of TRPA1 has been recently resolved, also having its open state is essential for understanding how this channel works. Here we use molecular dynamics simulations combined with electrophysiological measurements and systematic mutagenesis to predict and explore the conformational changes coupled to the expansion of the presumptive channel's lower gate. We show that, upon opening, the upper part of the sensor module approaches the pore domain of an adjacent subunit and the conformational dynamics of the first extracellular flexible loop may govern the voltage-dependence of multimodal gating, thereby serving to stabilize the open state of the channel. These results are generally important in understanding the structure and function of TRPA1 and offer new insights into the gating mechanism of TRPA1 and related channels.
Keywords: ankyrin receptor subtype 1; transient receptor potential; TRP channel; allyl isothiocyanate; sensor module; S1–S2 linker